Financial Risk Management - Endah Suci Damayanti; Adler Haymans Manurung; Nera Marinda Machdar (PT FORMOSA CENDEKIA GLOBAL, 2023)
The purpose of this article is to describe the existing variables by providing a corroboration from the literature articles from the findings. The research method used is qualitative by graphically depicting sources from existing journals related to this article. The findings derived from these scientific articles then the findings or results are reinforcement for this scientific article with regard to the variables used. Financial risk management in the context of digitalization has an important role in increasing company value and meeting customer expectations. Through the implementation of an effective digital strategy, financial institutions can optimize financial services, improve customer data security, and provide a better experience for customers. The importance of service quality in the digitalization context was also revealed, where good service quality contributes to customer satisfaction and their loyalty to the company. However, it is important to remember that digitization also carries its own risks, such as data security and financial transactions